2012
DOI: 10.3109/10428194.2012.688965
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leukemia and its impact on graduation and having children: results from a national survey

Abstract: To assess the level of graduation, the wish to have children and the course of pregnancy among former patients with childhood leukemia in comparison to the general German population and depending on gender, a nationwide survey was conducted in 2008. In total 63.6% (1476/2319) of the contacted survivors of childhood leukemia participated (mean age 25.7 years, range 19-43 years). Survivors graduated at higher levels of school compared to the general population, with 48.6% (female) versus 38.0% and 52.6% (male) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 21 publications
0
33
0
2
Order By: Relevance
“…Two studies had a prospective design and involved linkage of national cancer registration, education, and population data; the remainder were retrospective and were based on self‐report of educational attainment. The two linkage studies identified the comparable population without cancer; six studies compared cancer survivors' outcomes with data from individuals who participated in various surveys; two compared results for survivors with national data; and five recruited, and collected data from, cancer‐free control groups (siblings, classmates, or samples of the general population) . The number of childhood cancer cases included in the studies ranged from 51 to 2213.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies had a prospective design and involved linkage of national cancer registration, education, and population data; the remainder were retrospective and were based on self‐report of educational attainment. The two linkage studies identified the comparable population without cancer; six studies compared cancer survivors' outcomes with data from individuals who participated in various surveys; two compared results for survivors with national data; and five recruited, and collected data from, cancer‐free control groups (siblings, classmates, or samples of the general population) . The number of childhood cancer cases included in the studies ranged from 51 to 2213.…”
Section: Resultsmentioning
confidence: 99%
“…The number of childhood cancer cases included in the studies ranged from 51 to 2213. Ten studies included multiple types of cancer; two studies focused only on leukemia and a further two, which included multiple cancer types, reported subgroup analyses for leukemias and/or other blood cancers; one study included only CNS tumors, and a further three reported results for the subgroup with these tumors; one study included only Differentiated Thyroid Carcinoma (DTC) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le point de vue des parents sur leurs enfants est plus péjoratif que celui des professeurs et que l'autojugement [10,11]. Concernant les pathologies autres que TC, une étude allemande met en évidence un niveau de diplôme supérieur chez les patients ayant été atteints de leucémie comparés à la population générale [12]. Une équipe finlandaise a comparé les notes obtenues au « 9th grade » à l'âge de 16 ans avec une population contrôle.…”
Section: Facteurs De Risques D'échec Scolaireunclassified
“…Dans une étude allemande publiée en 2012, 1476 patients atteints de leucémie dans l'enfance et âgés de 19 à 43 ans ont été interrogés. Ils ont les mêmes souhaits de parentalité que la population générale (93,3 % des femmes et 89,3 % des hommes) mais ont moins souvent d'enfant (p < 0,001) malgré un taux d'avortement moindre (p < 0,001) [12]. Outre la radiothérapie et les chirurgies délabrantes, l'allogreffe de cellules souches peut, de par ses conséquences physiques et émotionnelles, provoquer des limitations dans la vie quotidienne et les relations interpersonnelles [17].…”
Section: Devenir Social Par Pathologieunclassified